Implementation of asthma guidelines to West Australian community pharmacies: an exploratory, quasi-experimental study. Issue 8 (31st August 2016) - Watkins, Kim; Trevenen, Michelle; Murray, Kevin; Kendall, Peter A; Schneider, Carl R; Clifford, Rhonda
Abstract : Objectives: Pharmacy assistants are often the first point of contact for patients presenting in community pharmacies. The current role of pharmacy assistants in the supply of asthma-reliever medications (short-acting β-agonists) was identified as a barrier to appropriate guideline-based care. The aim of this research was to devise and evaluate a team-based intervention to formalise the role of pharmacy assistants and to improve asthma guideline-based care in community pharmacy. Design: A controlled pre-post intervention study was conducted in 336 metropolitan pharmacies located in Perth, Western Australia. Pharmacies were stratified into 2 groups (187 intervention and 149 control) based on known confounders for asthma control. The intervention was designed using a common-sense approach and resources developed included a checklist, videos and web page. Delivery was via workshops (25 pharmacies) or academic detailing (162 pharmacies). Pharmacy practice was assessed preintervention and postintervention via covert simulated patient methodology. Primary outcome measures included patient medical referral, device use demonstration and counselling, internal referral and/or direct involvement of a pharmacist in consultations. Results: There was a significant increase in patient medical referral in intervention pharmacies from 32% to 47% (p=0.0007) from preintervention to postintervention, while control pharmacies showed a non-significant decrease from 50% to 44% (p=0.22). Device counselling was not routinely carried out at any stage or in any cohort of this research and no significant changes in internal referral were observed. Conclusions: Increases in medical referral indicate that asthma guideline compliance can be improved in community pharmacy if implementation employs a team-based approach and involves pharmacy assistants. However, results were variable and the intervention did not improve practice related to device counselling or internal referral/pharmacist involvement. Undertaking more workshops may have improved results. Guideline implementation in community pharmacy should consider the role of pharmacy assistants and how to overcome logistical barriers to pharmacy participation in implementation activities.